Caste,tribes & cultural of India: Bengal, Bihar and Orissa - Bahadur, K.P (Delhi, 1977)
The tribes which have been mainly taken up for study in this volume are the Bhuiya, Juang, Bauri, Bagdi, Ho, Bhumij, Munda, Kandh, Kharia, Kochh, Mahili, Oraon and Birhors. The Study of the manners and customs, origin, Tribal structure, Religion & folk-lore have vividly been described in this in depth study of the colourfull region. Perhaps no where else in the World will there be found such a richness of culture or such a wealth of heritage. This study of the tribal Indian sub-continent provides a venture which is fascinating, and that is why it attracted foreigners who have entered into this enchanting panorma right from the beginning. The matter comprised is indispensible and of permanent 'reference' shelf-value for all libraries, institutions or individuals connected with Anthropology, Ethenology, Geography, Human interest, Social Sciences, History and Tourism.
Keywords: Tribes India